Body Image Dissatisfaction in Patients with Inflammatory Bowel Disease. Issue 2 (February 2015) - Saha, Sumona; Zhao, Ying-Qi; Shah, Samir A.; Esposti, Silvia Degli; Lidofsky, Sheldon; Bright, Renee; Law, Meaghan; Moniz, Heather; Samad, Zahid; Merrick, Marjorie; Sands, Bruce E.
Abstract : Background: Despite the fact that the inflammatory bowel diseases (IBD) and their treatments may affect physical appearance, the effect of IBD on body image is poorly understood. The aims of this study were to determine whether body image dissatisfaction (BID) changes over time in patients with IBD and to examine the demographic and disease-related variables associated with decreased body image. Methods: Adults aged 18 and above in the Ocean State Crohn's and Colitis Area Registry with at least 2 years of follow-up were eligible for this study. All patients were enrolled within 6 months of IBD diagnosis and followed prospectively. BID was assessed using a modified version of the Adapted Satisfaction With Appearance questionnaire. Total Adapted Satisfaction With Appearance scores and 2 subscores were calculated. To assess for changes over time, general linear models for correlated data were used for continuous outcomes, and generalized estimating equations were used for discrete outcomes. Results: Two hundred seventy-four patients were studied. BID was found to be stable over time among men and women with IBD despite overall improvements in disease activity. No differences were found in BID according to IBD subtype. Female gender, greater disease activity, higher symptom burden, longer duration of steroid use, dermatologic and musculoskeletal manifestations of IBD, and ileocolonic disease location among patients with Crohn's disease were associated with greater BID. Greater BID was associated with lower health-related quality of life. Conclusions: BID remains stable in an incident cohort of IBD despite improved disease activity and is associated with lower health-related quality of life. Abstract : Article first published online 7 January 2015.